Feed Plants Selection and Nesting Site of Cuscus (Phalanger sp.) in Nature Reserve of Gunung Mutis, East Nusa Tenggara - WARTIKA ROSA FARIDA; TEGUH TRIONO; TRI HADI HANDAYANI; ISMAIL ISMAIL (Biodiversitas Journal of Biological Diversity, 2005)
Research on feed plants selection and nesting site of cuscus (Phalanger sp.) was conducted in Nature Reserve of Gunung Mutis, West Timor, East Nusa Tenggara. The study was done in the montane rain forest with the altitude of 1530-2010 m a.s.l. The results showed seven species of plants was selected by cuscus as their nesting site and 41 species of plants as their feed resources. Parts of the plants being consumed were young leaves, flower, and fruit. Their habitat was damaged caused by exploitation of the forest. Meanwhile, hunting pressure by local people to provide their meat supply threatens the existence of cuscuses.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Phalanger sp., cuscus, plant, feed, nesting site, Gunung Mutis, East Nusa Tenggara.